A regional approach to Nordic crop wild relative in situ conservation planning. Issue 2 (6th February 2019) - Fitzgerald, Heli; Palmé, Anna; Asdal, Åsmund; Endresen, Dag; Kiviharju, Elina; Lund, Birgitte; Rasmussen, Morten; Thorbjörnsson, Hjörtur; Weibull, Jens
Abstract: Crop wild relatives (CWR) can provide one solution to future challenges on food security, sustainable agriculture and adaptation to climate change. Diversity found in CWR can be essential for adapting crops to these new demands. Since the need to improve in situ conservation of CWR has been recognized by the Convention on Biological Diversity (CBD) (2010) and the Global Strategy for Plant Conservation (2011–2020), it is important to develop ways to safeguard these important genetic resources. The Nordic flora includes many species related to food, forage and other crop groups, but little has been done to systematically secure these important wild resources. A Nordic regional approach to CWR conservation planning provided opportunities to network, find synergies, share knowledge, plan the conservation and give policy inputs on a regional level. A comprehensive CWR checklist for the Nordic region was generated and then prioritized by socio-economic value and utilization potential. Nordic CWR checklist was formed of 2553 taxa related to crop plants. Out of these, 114 taxa including 83 species were prioritized representing vegetable, cereal, fruit, berry, nut and forage crop groups. The in situ conservation planning of the priority CWR included ecogeographic and complementarity analyses to identify a potential network of genetic reserve sites in the region. Altogether 971, 633 occurrence records of the priority species were analysed. A minimum number of sites within and outside existing conservation areas were identified that had the potential to support a maximum number of target species of maximum intraspecific diversity.